Biometric and ICL-related risk factors associated to sub-optimal vaults in eyes implanted with implantable collamer lenses - Santiago Cerpa Manito; Angel Sánchez Trancón; Oscar Torrado Sierra; António Manuel Baptista; Pedro Miguel Serra (Eye and Vision, 2021)
Abstract Background To identify biometric and implantable collamer lens (ICL)-related risk factors associated with sub-optimal postoperative vault in eyes implanted with phakic ICL. Methods This study reports a retrospective case series of the first operated eye in 360 patients implanted with myopic spherical or toric ICL. Preoperatively, white-to-white (WTW), central keratometry (Kc) and central corneal thickness (CCT) were measured using the Pentacam. Anterior-segment optical coherence tomography (AS-OCT, Visante) was applied preoperatively for measuring the horizontal anterior-chamber angle-to-angle distance (ATA), internal anterior chamber depth (ACD), crystalline lens rise (CLR), anterior-chamber angle (ACA) and postoperatively the vault. Eyes were divided into three vault groups: low (LVG: ≤ 250 μm), optimal (OVG: > 250 and < 1000 μm) and high (HVG: ≥ 1000 μm). Multinomial logistic regression (MLR) was used to find the sub-optimal vault predictors. Results MLR showed that CLR, ICL size minus the ATA (ICL size-ATA), age, ICL spherical equivalent (ICLSE) and ICL size as contributing factors for sub-optimal vaults (pseudo-R 2  = 0.40). Increased CLR (OR: 1.01, CI: 1.00–1.01) and less myopic ICLSE (OR: 1.22, CI: 1.07–1.40) were risk factors for low vaults. Larger ICL size-ATA (OR: 41.29, CI: 10.57–161.22) and the 13.7 mm ICL (OR: 7.08, CI: 3.16–15.89) were risk factors for high vaults, whereas less myopic ICLSE (OR: 0.85, CI: 0.76–0.95) and older age (OR: 0.92, CI: 0.88–0.98) were protective factors. Conclusion High CLR and low ICLSE were the major risk factors in eyes presenting low vaults. In the opposite direction, ICL size-ATA was the major contributor for high vaults. This relationship was more critical in higher myopic ICLSE, younger eyes and when 13.7 mm ICL were used. The findings show that factors influencing the vault have differentiated weight of influence depending on the type of vault (low, optimal or high).